P2 5 Sandy Spectrum - Rowlett, Edward; Corbett, Charlie; Kaur, Ish (Physics Special Topics, 2024)
In this paper we investigate the velocities required for an hourglass containing yellow sand to appear each colour in a rainbow to a stationary observer. Additionally, we calculated the difference in duration the hourglass would appear to have if it were travelling at that velocity.